Mycosis Fungoides: Case Report and Literature Review - Akinsegun A. Akinbami (Clinical Medicine Insights: Case Reports, 2014)
Mycosis fungoides (MF), also known as Alibert-Bazin syndrome or granuloma fungoides, is the most common form of cutaneous T-cell lymphoma. Cutaneous lymphomas are an uncommon, heterogeneous group of non-Hodgkin lymphomas (NHLs) of T- and B-cell origin where the skin is the primary organ of involvement. This is a case of a 60-year-old Nigerian woman, who was diagnosed and managed as a case of chronic dermatitis but further investigations confirmed a diagnosis of MF; she was thereafter managed with topical glucocorticoids/chemotherapy and improved on these treatments. We make a plea for better awareness of the disease among physicians and pathologists in Africa.